PENERAPAN TEKNOLOGI PAPER QUILLING DENGAN MEMANFAATKAN SAMPAH KERTAS UNTUK MENINGKATKAN KETRAMPILAN PETUGAS KEBERSIHAN DI UNIVERSITAS ANDALAS - Olly Norita Tetra; Bustanul Arifin; Deswati Deswati (LPPM Universitas Andalas, 2023)
Paper waste is the most common waste generated from academic activities on the Andalas University campus. So far, paper waste is allowed to accumulate and then sold by cleaners to waste collectors or burned. This activity aims to increase women's resources and potential through Qulling Paper technology with promising business opportunities, especially for cleaning workers. This activity was carried out from July to September 2022, with the target participants being cleaners with direct contact with paper waste. The method used is counseling about the dangers of paper waste to the environment and health, which ends with discussions and interviews to determine the level of knowledge of cleaning workers about the management and processing of paper waste. The activity continued with paper waste processing training through paper quilling technology by practicing directly until the participants could produce a craft product. Mentoring activities for participants are also carried out by guiding them until they are skilled at producing craft products worth selling. In this training activity, all activity participants can produce handicraft products that have high selling value and are economical. Paper waste processing training for cleaners is one of the most appropriate solutions for reducing the amount of paper waste on the Andalas University campus and, at the same time, improving skills. It is hoped that this activity can increase knowledge and skills and reduce the amount of paper waste in the Andalas University campus environment.